RETHINKING THE NEW INTERNATIONAL DIVISION OF LABOUR THROUGH THE LENS OF GENDER AND CLASS DIFFERENCES: GARMENT INDUSTRY AND PRISON LABOUR (Annual of the Faculty of Philosophy in Skopje, 2019)
This paper pays attention to the socio-economic aspect of the so-called “newinternational division of labour” or “global value chains” from a gender perspective.It analyses the garment industry and the prison labour known as “prison industrialcomplex” as part of the structuring and the division of labour on a global scale. Drawingfrom theories and research on global development, neo-marxist feminist theory,as well as the current events taking place in the economy and labour market, thiswork argues that the “new” international division of labour is unsustainable andharmful for women around the world in particular and for all socially vulnerable categoriesof people in general. At the same time, this paper presents the necessity for agender sensitive policy-making that takes into account the specific context whichboth women and men are situated in, as well as the specific gendered effects emergingfrom the socio-economic politics of global development.